Media Sosial Sebagai Lingkungan Sosial Anak: Studi Tentang Pembentukan Sikap Akhlakul Karimah - Mulyana, Ida (Jurnal Community, 2023)
A child, in accordance with the direction of Islam, is the basic foundation for the growth of the child in the next phase. The aim of the research is to provide an overview of moral education in social media for children. The methods used in this research is qualittative analysis. Research shows that early education plays an important role for children. A weak moral foundation will make children vulnerable to negative things. The presence of communication technology has had a positive impact on the lives of children in learning and socializing, but not the least negative impact it can have. Since childhood, children have been introduced to communication technology, both as a means of play, entertainment, learning and as a way of communicating with parents, peers, and older people. Islam guides the good in human life through the Quran and the Hadith of the Prophet Muhammad SAW. Good morals are a filter for children in the use of communication technology well. Children tend to imitate the many examples they see, so education plays an important role in providing knowledge, training, accustoming and facilitating good morals in the use of communication technology. It is not only the teacher who is responsible, but also the teacher and his parents.